2015
DOI: 10.1177/1461444815600412
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating journalistic routines in a digital age: A review of research on the use of online sources

Abstract: This review article provides a critical discussion of empirical studies that deal with the use of online news sources in journalism. We evaluate how online sources have changed the journalist–source relationship regarding selection of sources as well as verification strategies. We also discuss how the use of online sources changes audience perceptions of news. The available research indicates that journalists have accepted online news sourcing techniques into their daily news production process, but that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(98 citation statements)
references
References 57 publications
2
83
0
13
Order By: Relevance
“…So far, online sources have not substituted offline sources, they rather serve as supplemental gimmick in the daily news sourcing process (Lecheler and Kruikemeier, 2016). To describe public relations information that are re-warmed by journalists and then conveyed in traditional media, Davies (2009) coined the expression "churnalism".…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, online sources have not substituted offline sources, they rather serve as supplemental gimmick in the daily news sourcing process (Lecheler and Kruikemeier, 2016). To describe public relations information that are re-warmed by journalists and then conveyed in traditional media, Davies (2009) coined the expression "churnalism".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, journalists hesitate to use information retrieved from social media as direct and quoted sources in news reporting (Lecheler and Kruikemeier, 2016). Because online sources so far have not substituted offline sources, they rather serve as a supplemental gimmick in the daily news-sourcing process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This also happened during the Brussels attacks. A recent review showed that journalists frequently use online sources for their research and that Twitter is particularly popular among those (Lecheler & Kruikemeier, 2015). Online sources like Twitter have become increasingly important, making it easier for journalists to research certain issues and quickly obtain information (Moon & Hadley, 2014).…”
Section: Changing Journalismmentioning
confidence: 99%
“…As a consequence, journalists are not only under pressure to follow suit, but may also consider social media a cost-efficient information source. Indeed, research shows that journalists increasingly use online and social media as news sources (Lecheler and Kruikemeier 2016;Broersma and Graham 2012). Messner and DiStaso (2008), for instance, show that The New York Times and The Washington Post increasingly rely on web blogs as sources.…”
Section: Introductionmentioning
confidence: 99%